Croisements paysage/danse/musique : écritures entre composition et improvisation - Mathilde Christmann (Projets de Paysage)
The conception in landscape is confronted to the difficulty to write a material which is in a perpetual motion. This issue tackles also, among other things, the disciplines of dance and music. One of the writing tools of the latter is the score – the role of which is devolved to composing. But in the second half of the 20th century, and following the impetus of the “open works”, some music scores willing to link composition and improvisation have appeared. These researches will influence the American landscaper Lawrence Halprin who will work on scores for the landscape and urban conception. Through the study of three creative devices – Lawrence Halprin in landscape, Mauricio Kagel in music, and Myriam Gourfink in dance – the issue of tension between composition and improvisation opened to motion is raised.